2019
DOI: 10.1089/rej.2018.2144
|View full text |Cite
|
Sign up to set email alerts
|

Red Blood Cell Distribution Width, Vascular Aging Biomarkers, and Endothelial Progenitor Cells for Predicting Vascular Aging and Diagnosing/Prognosing Age-Related Degenerative Arterial Diseases

Abstract: The emerging evidence emphasizes Red blood cell distribution width (RDW) as optimal prognostic biomarker for cardiovascular diseases. However, several clinical biases impede its clinical application. Recent recommendations suggest combining RDW with other biomarkers. Accordingly, we propose evaluating the wellrecognized biomarkers of vascular aging (i.e., the leukocyte telomere length and telomerase activity, and reduced levels of endothelial progenitor cells [EPCs]) with RDW, for predicting the risk for vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…In a study from the NHANES, it was even reported that RDW was a better predictor of CHD mortality than high sensitivity C-reactive protein (hsCRP) 15 . In addition, in a cross-sectional study of patients diagnosed with aneurysms of the ascending aorta, positive correlations were also found between RDW values and systemic inflammatory molecules, including hsCRP, IL-6, TNF-α, MMP-2, and MMP-9 levels 16 . On the other hand, inflammation is suggested to be involved in the pathological processes of AAA 17,18 .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a study from the NHANES, it was even reported that RDW was a better predictor of CHD mortality than high sensitivity C-reactive protein (hsCRP) 15 . In addition, in a cross-sectional study of patients diagnosed with aneurysms of the ascending aorta, positive correlations were also found between RDW values and systemic inflammatory molecules, including hsCRP, IL-6, TNF-α, MMP-2, and MMP-9 levels 16 . On the other hand, inflammation is suggested to be involved in the pathological processes of AAA 17,18 .…”
Section: Discussionmentioning
confidence: 90%
“…It is well known that blood clots can occur in aortic aneurysms due to altered flow conditions, and that such thrombi have potential biochemical and biomechanical effects on both blood components and the aortic wall 26,27 . AAA could also be associated with impaired endothelial function and other features of vascular aging 16 , which in turn, could cause mechanical stress to the erythrocytes. Hypothetically, early vascular changes in individuals with high risk of AAA could affect the life span of the red cells and thereby the RDW.…”
Section: Discussionmentioning
confidence: 99%
“…Для этого были отобраны 80 пожилых (72±4,8 лет) и 80 молодых (26,2±3,4 лет) здоровых пациентов и 80 пациентов с сердечно-сосудистыми патологиями. Полученные основные результаты показали, что повышенные значения ширины распределения эритроцитов по объему наряду с повышенными уровнями высокочувствительного С-реактивного белка в крови и сниженные средние значения длины теломер в лейкоцитах, АТ и EPC независимо связаны с высоким риском старения сосудов [20].…”
Section: влияние на биологию теломер -возможный путь к замедлению стаunclassified
“…Accurate risk assessment of an individual's propensity to develop CVDs is essential for personalized health care and primary prevention of these conditions. An increasing number of novel biomarkers have been linked to CVD risk [3][4][5][6][7][8][9][10][11][12][13][14], implying their critical role in precise risk assessment for heterogeneous CVDs. Current established functions for CVD risk stratification are either based only on conventional risk factors or include a limited number of biomarkers [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%